THE ROLE OF MICROFINANCE IN ENHANCING ENTREPRENEURIAL GROWTH IN SUB-SAHARAN AFRICA: A COMPARATIVE ANALYSIS OF NIGERIA AND KENYA - Abubakar, Abdulsalami (UIN Sunan Gunung Djati Bandung, 2022)
This study explores the role of microfinance in enhancing entrepreneurial growth in Sub-Saharan Africa, focusing on a comparative analysis between Nigeria and Kenya. Microfinance has emerged as a crucial tool for economic empowerment in developing regions, particularly for fostering entrepreneurship. The research is grounded in existing literature, examining how access to microfinance services impacts entrepreneurial development in both countries. Nigeria and Kenya serve as significant case studies due to their distinct economic landscapes and microfinance penetration levels. The findings suggest that microfinance significantly contributes to entrepreneurial growth, albeit with varying degrees of effectiveness influenced by local economic policies and infrastructure. The study also highlights the challenges faced by microfinance institutions, such as high-interest rates and inadequate financial literacy among borrowers. The comparative analysis reveals that while both countries benefit from microfinance, Kenya demonstrates more robust outcomes due to better regulatory frameworks. This paper contributes to the ongoing debate on optimizing microfinance for sustainable entrepreneurial growth in emerging economies. Future research should focus on policy interventions that can enhance microfinance effectiveness across different contexts.